POLITICAL ELITES REBELLION AND ITS IMPACT ON SOUTH SUDAN - Chol Riak, Jacob Dut; Taban Dada, Moses Lemi (International Journal of Research -GRANTHAALAYAH, 2026)
Since it’s gained her independence in 2011, South Sudan has been plagued by political instability, largely driven by the actions and rebellions of its political elites. This research investigates the underlying motivations behind these elite-led uprisings and their wide-reaching impact on the country's socio-political landscape. The study identifies key drivers such as power struggles, ethnic divisions, corruption, and the competition for control over natural resources, particularly hydrocarbons. These conflicts, often fueled by personal and ethnic grievances, have perpetuated cycles of violence, destabilizing governance and hindering development efforts. The effects of these rebellions have been devastating for the civilian population. The research highlights the severe humanitarian crisis marked by mass displacement, economic hardship, the destruction of infrastructure, and widespread human rights abuses. The study also underscores the psychological trauma and social disintegration caused by ongoing conflicts. Additionally, it sheds light on how these rebellions have disrupted essential services such as healthcare and education, exacerbating poverty and inequality. Through a combination of qualitative and quantitative methodologies, the research provides a nuanced analysis of the visible and invisible impacts of elite rebellions. It concludes that achieving sustainable peace and political stability in South Sudan requires addressing the root causes of conflict. Proposed solutions include inclusive dialogue among political elites, governance reforms to combat corruption and enhance transparency, and reconciliation initiatives to heal historical grievances. The study further emphasizes the importance of international support and the implementation of power-sharing agreements as pathways toward conflicts resolutions. This research contributes to the broader academic discourse on political instability and elite behavior in post-colonial states, offering insights that could inform policy interventions and peace building efforts in South Sudan and other similar contexts.